5.10 Using detailed clinical nutritional data to predict optimal energy and protein intakes for preterm infants. (9th June 2014) - Johnson, MJ; Pond, JP; Pearson, F; Emm, A; Leaf, AA
Abstract : Background: Preterm infants often experience poor growth during the neonatal period, and are discharged with weights and head circumferences on centiles well below that on which they were born. One reason for this is inadequate nutrient provision. Whilst recommendations for nutrient intakes exist, their validity is the subject of debate, and there is a need to better understand optimal nutrient intakes for these infants. Methods: Detailed nutrient intake and growth data collected on preterm infants as part of another study was used. Growth was assessed using the difference in standard deviation score (dSDS) for weight and head circumference between birth and discharge. Linear regression of growth and mean intakes of protein and energy during hospital stay was carried out, and optimal intakes were then estimated assuming that ideal growth would result in a dSDS of zero. Results: 186 preterm infants were included, with a mean (SD) gestational age and birth weight of 28.6(2.8) weeks and 1.01(0.28)kg. Mean intakes of energy and protein were significantly associated with weight dSDS, with coefficients (95% confidence intervals) of 0.01 (0.001–0.020) and 0.56 (0.307–0.818) respectively. Using regression constants, this equates to estimated optimal intakes of 174 kcal/kg/day and 4.11 g/kg/day protein. However, r 2 values were low at 0.02 and 0.09 respectively. Conclusions: This study demonstrates the utility of detailed clinical nutritional data in studying the relationships between intake and growth. Whilst r 2 values were low, these findings suggest that energy and protein intakes required for growth along birth centile line may be higher than those currently recommended, and warrant further investigation.